Telling tails - Ryan, Sofie, 1958- (Ryan, Sofie, 1958- Second Chance cat mystery., 2017)
"The New York Times bestselling author of A Whisker of Trouble returns as secondhand shop owner Sarah Grayson and her rescue cat, Elvis, get caught up in a case of she said, she said... When Sarah Grayson opened a secondhand shop in the quaint town of North Harbor, Maine, she was expecting peace and quiet. Then she was adopted by a rescue cat named Elvis and a kooky trio of senior sleuths known as Charlotte's Angels. Now she has nine lives worth of excitement... Sarah's friend and employee Rose is delivering a customer's purchase when the quick errand becomes a deadly escapade. Rose arrives just in time to see the customer murdered by his wife, but before she can call the police, she is knocked out cold. When she wakes up, no one believes her, especially after the woman claims her husband is very much alive and has left her for someone else--and has a text message and empty bank account to prove it. Despite her convincing story, Sarah is sure something is fishy--and it's not Elvis's kitty treats. Sarah, Elvis, and the Angels are determined to unravel this mysterious yarn, before the feral killer pounces again..."--Publisher's website.